Gambaran Perilaku dan Pengetahuan Operator Terhadap Treatment Produk dan Penanganan Runner Devisi Injection Molding di PT. ARPS - M. Herdin Fatwa Toga Putra; Akas Yekti Pulih Asih; Bagus Wicaksono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The cosmetic container processing industry produces waste (runner) for each processing process. if the waste exceeds the storage capacity of above 10cm of the barrel runner, it will have the potential to cause work accidents such as the runner getting stuck in the body (eyes and feet). After making observations, many operators often forget to check the waste storage bins regularly. Therefore, the EHS conducted further briefings regarding product treatment and runner handling before starting work. To find out the description of the operator's knowledge of product treatment PPE and runner handling in the injection molding division of PT. ARPS. This study used a descriptive quantitative study with a cross-sectional approach and data collection was carried out by observation and questionnaires. March 2023. PT. Albea Rigid Packaging Surabaya, Jl. Rungkut Industry IV No.23, Rungkut Tengah, Gunung Anyar District, Surabaya City, East Java 60293. 35% of respondents were >30 years old and 65% were <30 years old. Working period >5 years amounted to 72%, and <5 years amounted to 28% with a duration of 8 hours of work. From the results of the analysis of the scattered questionnaires, the total score was (often) = 876, (rarely) = 176, (never) = 20. Then the overall score is added up and produces a score of 1,072 (very good) out of a total score of 1,200. The operator's knowledge questionnaire on product treatment and runner handling obtained a score of 1,072 with a total percentage of 89.33% with very good indicators.